Implementasi Media Video Youtube dalam Pembelajaran PPKn untuk Meningkatkan Motivasi Belajar Siswa Kelas VI MI Miftahul Abror - Abd. Azis Tata Pangarsa (MODELING: Jurnal Program Studi PGMI, 2020)
Based on the results of observations by the author, it shows that the majority of sixth grade students in the academic year 2019/2020 MI Miftahul Abror are students who have intelligent characteristics and have a high curiosity, with a background of village children but are accustomed to using gadged, mobile or laptop to access the internet. On the other hand, the development of technology is developing quite rapidly, so that this development has changed the paradigm of the community in seeking and obtaining information, which is no longer limited to newspaper, audio-visual and electronic information, but also other sources of information, one of which is through Internet Network.To help and facilitate teaching, teachers can utilize technology to be able to develop interactive and integrative learning media tailored to the needs and learning material being taught. For that reason, it is necessary to use the internet as a learning medium in this case I use YouTube videos in PPKn learning to improve student motivation in class VI MI Miftahul Abror Karangploso Malang Regency.The purpose of writing this journal is to know and understand about:1. The steps of making youtube video media in PPKn learning to increase students' motivation in class VI MI Miftahul Abror.2. Implementation of YouTube video media in PPKn learning to improve student motivation in class VI MI Miftahul Abror.3. Knowing the evaluation of YouTube video media in PPKn learning to improve student motivation in class VI MI Miftahul Abror.With these learning media proven able to increase students' motivation and learning achievement.